Physical dysfunction practice skills for the occupational therapy assistant - Early, Mary Beth
Designed as both a practical clinical reference and a comprehensive classroom text, the second edition of Physical dysfunction practice skills for the occupational therapy assistant offers a focused, easy-to-use approach to physical dysfunction. This new edition provides updated and expanded coverage of issues related to work, habits of health and wellness, leisure and social participation, and activities and occupations of daily living